Pola makan, obesitas, dan frekuensi serangan pada pasien artritis gout - Fatimah Az-zahra; Dedy Nurwahid; Retno Pangastuti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2014)
Background: Trend of gout arthritis prevalence is increasing every year. Obesity, high purine diet, especially from an animal source, are some risk factors for recurrent gout attacks.Objective: To evaluate the relationship between diet, obesity, and frequency of gout flares in gout arthritis patients.Method: This study was a cross-sectional study with patients from RSUP Dr. Sardjito, RSUD Wirosaban, RSUD Panembahan Senopati that ever diagnosed as gout arthritis within February 2010 - February 2012 which can be seen in the medical record and live in Special District of Yogyakarta with the full address provided, as the respondents of this study. The home visit was done for dietary assessment, waist circumference measurement, and interviewing the respondent about gout flares frequency during the last year.Results: Vitamin C consumption in the 1st and 2nd tertiles increase the odds to have any gout flare (OR=5.5; 95% CI: 1.08-27.77 and OR=1.5; 95% CI: 0.29-7.35, respectively). Obesity tends to increase the odds of having any gout flares up to 1.4 times (95% CI: 0,38-5,25).Conclusion: Low consumption of vitamin C significantly increases the odds of having any gout flares. The odds is also higher in patients with obesity, though this relationship is statistically insignificant.